Chocolate fever - Smith, Robert Kimmel, 1930-2020; Fiammenghi,Gioia,illus (New York : Scholastic, 1972)
From eating too much chocolate, Henry breaks out in brown bumps that help him foil some hijackers and teach him a valuable lesson about self-indulgence.
Includes "Literature Circle" questions.
Accelerated Reader AR
Keywords: Chocolate -- Fiction; Humorous stories